Complications and risk factors in transrectal ultrasound-guided prostate biopsies - Jesus, Carlos Márcio Nóbrega de (2006)
CONTEXT AND OBJECTIVE: Prostate biopsy is not a procedure without risk. There is concern about major complications and which antibiotics are best for routine use before these biopsies. The objective was to determine the rate of complications and the possible risk factors in prostate biopsies. DESIGN AND SETTING: Prospective study, Facul- dade de Medicina de Botucatu. METHODS: Transrectal ultrasound (TRUS) guided prostate biopsies were carried out in 174 patients presenting either abnormality in digital rectal ex- aminations (DRE) or levels higher than 4 ng/ml in prostate-specific antigen (PSA) tests, or both. RESULTS: Hemorrhagic complications were the most common (75.3%), while infectious complications occurred in 19% of the cases. Hematuria was the most frequent type (56%). Urinary tract infection (UTI) occurred in 16 patients (9.2%). Sepsis was observed in three patients (1.7%). The presence of an indwelling catheter was a risk factor for infec- tious complications (p < 0.05). Higher numbers of biopsies correlated with hematuria, rectal bleeding and infectious complications (p < 0.05). The other conditions investigated did not correlate with post- biopsy complications. CONCLUSIONS: Post-biopsy complications were mostly self-limiting. The rate of major complications was low, thus showing that TRUS guided prostate biopsy was safe and effective. Higher numbers of fragments taken in biopsies correlated with hematuria, rectal bleeding and infectious complications. An indwelling catheter represented a risk factor for infectious complica tions. The use of aspirin was not an absolute contraindication for TRUS.